Application of TLS Intensity Data for Detection of Brick Walls Defects. Issue 2 (September 2019) - Suchocki, Czesław; Katzer, Jacek; Serrat, Carles; Jagoda, Marcin
Abstract: Terrestrial Laser Scanning (TLS) is a well-established technique for remote acquisition of geometrical data of a tested object. For the past two decades it has been commonly used in geodesy, surveying and related areas for acquiring data about spacing of civil engineering structures and buildings. An average TLS apparatus, apart from 3D coordinates registers radiometric information of laser beam reflectance. This radiometric information of the laser beam reflectance is usually called intensity and has no meaning for solely geometric measurements. Nevertheless, the value of intensity depends mainly on physicochemical properties of scanned material such as roughness, colour and saturation. Keeping these facts in mind, authors suggest using changes in value of intensity to locate various imperfections on a brick wall. So far, authors have conducted a thorough and successful research programme dedicated to detection of saturation and saturation movement in brick walls. Based on this experience a new research programme was conducted focused on various aspects of detection of brick wall defects. The main aim of the paper is to present the possibility of using the intensity value in for the diagnostics of the technical condition of a brick walls. Advantages and limitations of harnessing TLS for detection of surface defects of brick walls are presented and discussed in the paper.